A novel magnetic countertraction device for endoscopic submucosal dissection significantly reduces procedure time and minimizes technical difficulty - Aihara, Hiroyuki; Ryou, Marvin; Kumar, Nitin; Ryan, Michele B.; Thompson, Christopher C. (Endoscopy, 2014)
Background and study aims: In endoscopic submucosal dissection (ESD), effective countertraction may overcome the current drawbacks of longer procedure times and increased technical demands. The objective of this study was to compare the efficacy of ESD using a novel magnetic countertraction device with that of the traditional technique. Methods: Each ESD was performed on simulated gastric lesions of 30 mm diameter created at five different locations. In total, 10 ESDs were performed using this novel device and 10 were performed by the standard technique.Results: The magnetic countertraction device allowed directional tissue manipulation and exposure of the submucosal space. The total procedure time was 605 ± 303.7 seconds in the countertraction group vs. 1082 ± 515.9 seconds in the control group (P = 0.021). Conclusions: This study demonstrated that using a novel magnetic countertraction device during ESD is technically feasible and enables the operator to dynamically manipulate countertraction such that the submucosal layer is visualized directly. Use of this device significantly reduced procedure time compared with conventional ESD techniques.